Interpreting Life as a Single Mother: A Phenomenological Study on the Experience of Early Adult Women in Kadujajar Village, Lebak Regency - Muhammad Faisal Ramadhan Sidi; Diva Natasyah (Journal of Sustainable Community Development, 2024)
The phenomenon of single motherhood has become an increasingly common social reality, bringing various psychological, social, and economic consequences. This study aims to explore the lived experiences, meanings, and challenges faced by single mothers in early adulthood in Kadujajar Village, Lebak Regency, Indonesia. The study employed a qualitative approach using the Interpretative Phenomenological Analysis (IPA) method within a constructivist paradigm. Participants were selected through snowball sampling and consisted of women aged 20–40 years who had been single mothers for at least one year and had at least one child. Data were collected through semi-structured in-depth interviews, observations, and documentation. The findings revealed three major themes: experiences of dual roles, meaning-making of single motherhood, and challenges and coping strategies. The results indicate that single mothers face substantial burdens as both primary caregivers and family breadwinners, resulting in economic, social, and emotional pressures. Nevertheless, participants were able to construct positive meanings from their experiences through self-acceptance, increased independence, and a strong sense of responsibility toward their children. Coping strategies included family support, spiritual strengthening, and efforts to achieve economic self-reliance. The study concludes that the experience of becoming a single mother in early adulthood represents a process of self-transformation that fosters resilience, personal growth, and the development of a new identity in coping with life challenges.